Board effectiveness and financial sustainability of non-profit organizations - Norazlin, Ahmad (Universiti Malaysia Pahang, 2018)
The purpose of this study is to examine the influence of board effectiveness on the level of financial sustainability for NPOs in Malaysia. Identifying the level of financial sustainability in NPOs is important in predicting their survival. In this study, 202 NPOs registered under Companies Commission of Malaysia (CCM) had been chosen for the financial period 2011. Financial sustainability indicators are equity ratio, revenue concentration, administrative cost ratio and operating margin ratio. While the board effectiveness represented by board planning effectiveness and board characteristics. The result of this study found that only Board Characteristics had significant and positive relationship with the financial sustainability of organizations. Overall, the findings in this study provide useful information to regulators in their continuous efforts to improve financial sustainability in the non-profit sector.